Effects of visual arts-based interventions on physical and psychosocial outcomes of people with stroke: A systematic review and meta-analysis - Mimi Wai Man Chan; Suzanne Hoi Shan Lo; Janet Wing Hung Sit; Kai Chow Choi; An Tao (Elsevier, 2023)
Background: Stroke is the leading cause of disability worldwide. People with stroke face a variety of physical and psychosocial issues as a result of their disability. Visual arts-based interventions refer to providing participants with structured visual arts-based activities and non-judgemental and safe environments to improve their health-related outcomes. Recent evidence showed that visual arts-based interventions had the potential to promote the holistic well-being of people with stroke. However, evidence of the effects of visual arts-based interventions on physical and psychosocial outcomes of people with stroke is limited. Objective: (1) To investigate the effects of visual arts-based interventions on physical and psychological outcomes in people with stroke, and (2) to identify the effective regimen of visual arts-based interventions to improve physical and psychosocial outcomes in people with stroke. Design: A systematic review and meta-analysis. Setting: Not applicable. Participants: 483 people with stroke were included in this review. Methods: Fourteen English and five Chinese databases were searched from the date of their inception to February 2022 using keywords based on the Population, Intervention, Comparison, Outcome, and Study framework. Two reviewers independently assessed trial eligibility and risk of bias and extracted data. Methodological quality was assessed using the revised Cochrane risk of bias tool for randomised trials. Meta-analysis was conducted using Review Manager 5.4. Narrative synthesis was performed when meta-analysis was inappropriate to conduct. The Grading of Recommendations, Assessment, Development, and Evaluation Approach was used to assess the certainty of evidence. Results: Seven randomised controlled trials were included. A meta-analysis reported statistically significant effects of visual arts-based interventions on depressive symptoms (Standardized mean difference [SMD]: −1.14, 95% confidence interval [CI]: −1.67 to −0.61; three studies; moderate quality of evidence), activities of daily living (SMD: 0.96, 95% CI: 0.24 to 1.69; four studies; low quality of evidence), and upper limb function (SMD: 0.83, 95% CI: 0.42 to 1.24; two studies; low quality of evidence). Conclusions: Visual arts-based interventions have favourable effects on depressive symptoms, activities of daily living, and upper limb function of people with stroke. However, the quality of evidence ranged from very low to moderate. Limited evidence suggested the effective regimen of visual arts-based interventions. Further rigorous randomised controlled trials should be developed to strengthen the relevant evidence. Registration: Registered at the International Prospective Register of Systematic Reviews on 11 July 2022 (Number: CRD42022334646).